The Homo Translator: Expanding the Borders of Translation - Salazar Valenzuela, Álvaro. (Universidad de Antioquia, 2022)
This paper is intended to be a reflection related to the homo translator as a translation change agent, from a philosophical perspective, not only from translation as a practical discipline, but from translation or translatology regarding the processes of change entailed in all things related to the “trans”: transfer, transformation or transmutation that moves from the linguistic to the social, ecological, etc., at the same time expanding the boundaries of translation theory which drives the translator to a rupture between his or her practical labor and the translatology’s scope of interest. Such a rupture in the task of the translator appears in a moment of axis shift in translation studies. Questions arise, then, such as does the homo translator have to settle for the sole task of transfer between languages? What happens with the other languages? Will the task of the translator have relevance if translatology extends its own borders?
L’homo translator et l’élargissement des limites de la traduction
El homo translator y la expansión de los límites de la traducción
Keywords: Homo translator; Philosophy of translation; Post-translation studies; Task of the translator; Tanslatology